Transcriptome and metabolome analysis reveal key genes and metabolic pathway responses in Leersia hexandra Swartz under Cr and Ni co-stress - Fu, Yuexin; Lin, Yi; Deng, Zhenliang; Chen, Mouyixing; Yu, Guo; Jiang, Pingping; Zhang, Xuehong; Liu, Jie; Yang, Xuemeng (Journal of hazardous materials, 2024)
Phytoremediation, an eco-friendly approach for mitigating heavy metal contamination, is reliant on hyperaccumulators. This study focused on Leersia hexandra Swart, a known chromium (Cr) hyperaccumulator with demonstrated tolerance to multiple heavy metals. Our objective was to investigate its response to simultaneous Cr and nickel (Ni) stress over 12 days. Results from physiological experiments demonstrated a significant increase in the activities of antioxidant enzymes (APX, SOD, CAT) and glutathione (GSH) content under Cr and Ni stress, indicating enhanced antioxidant mechanisms. Transcriptome analysis revealed that stress resulted in the differential expression of 27 genes associated with antioxidant activity and metal binding, including APX, SOD, CAT, GSH, metallothionein (MT), and nicotinamide (NA). Among them, twenty differentially expressed genes (DEGs) related to GSH metabolic cycle were identified. Notably, GSTU6, GND1, and PGD were the top three related genes, showing upregulation with fold changes of 4.57, 6.07, and 3.76, respectively, indicating their crucial role in metal tolerance. The expression of selected DEGs was validated by quantitative real-time PCR, confirming the reliability of RNA-Seq data. Metabolomic analysis revealed changes in 1121 metabolites, with amino acids, flavonoids, and carbohydrates being the most affected. Furthermore, glucosinolate biosynthesis and amino acid biosynthesis pathways were represented in the KEGG pathway of differentially expressed metabolites (DEMs). This study provides insights into the tolerance mechanisms of L. hexandra under the co-stress of Cr and Ni, offering a new perspective for enhancing its remediation performance. [Display omitted] •Novel tolerance mechanisms in L. hexandra have been analyzed.•Co-stress with Cr and Ni increased amino acid and flavonoid content in L. hexandra.•Upregulation of ABCC10, SODCC2, GSTM1, and NAS3 contributes to Cr and Ni tolerance.•GSH metabolic pathways and TCA cycle are vital for Cr and Ni detoxification.